Особенности приграничного сотрудничества Санкт-Петербурга и регионов Юго-Восточной Финляндии - Mezhevich, Nikolai M.; Spiridonova, Veronika (Administrative Consulting, 2025)
Cross-border cooperation between Finland and Russia is one of the priorities of international integration relations between our country and the European Union. The purpose of this article - the study of inter-regional cooperation between Russia and Finland in the aspect of development projects and programs to strengthen external relations and cross-border cooperation European Union. In accordance with the purpose of the study seeks to analyze the features of cross-border cooperation between St. Petersburg and regions of South-Eastern Finland (Kymenlaakso, South Karelia), implemented in the framework of the ENPI PPP projects. The article has a theoretical and practical interest for specialists studying cross-border cooperation. The essence and manifestation of the processes of cross-border cooperation between St. Petersburg and regions of South-Eastern Finland within the framework of the ENPI PPP are revealed. It was concluded that the program ENPI CBC have a positive effect on the development of cross-border contacts between St. Petersburg and the regions of South-Eastern Finland. It is advisable to continue the dialogue between Russia and Finland to expand their application and qualitative development of the zone.